The Presence of New Applications in Product Marketing Activities: What is MSME Readiness and Response - Gunawan Widjaja (Enrichment : Journal of Management, 2022)
The emergence of various new business and product marketing applications is increasingly unstoppable. So business drivers must be able to adapt to the emergence of various applications which are, of course, ready to succeed in business, especially marketing matters based on instantaneous internet connections. This study seeks various views of experts on the emergence of various technology applications in the business arena, especially marketing. For this reason, we have conducted data searches on literature sources that discuss new technology issues in business marketing. The sources include publications of both books and other scientific works that actively discuss technology issues in innovating business marketing. We carry out this study under a phenomenological approach, a strategy to analyze or get input or data findings that can answer problems from a relatively large amount of data. For example, in this study, we carried out a data coding system that carefully evaluated and interpreted the data so that the data became valid and reliable findings, which are the characteristics of qualitative study data analysis. Finally, based on the findings and discussion of the results, we can conclude that the emergence of various applications of the latest technology, especially in the context of marketing MSME products, has required business people to be more proactive in studying and applying the latest technology models which have generally been successful in promoting and marketing MSME products and services. Thus, we hope that the findings of this business and marketing study will be valuable inputs in efforts to maximize future similar studies by academics and industry.